MODERN VE POSTMODERN DÜŞÜNCELERDE BİLİM - Ramazan Ertürk (Felsefe Dünyası)
It is often said that science is the method to be followed in order to achieve truth. But science itself is understood variously in various epochs. Hence arises the question: Which science? And, even, for which truth? This article aims at investigating and —to some degree companing and constrasting two concepts of science: Modern and Postmodern. The main question for which an answer is searched here is this; What are the modern and postmodern concepts of science as true method s for truth.